Integration and Application of a Fabric-Based Modified Cam-Clay Model in FLAC3D - Xiao-Wen Wang; Kai Cui; Yuan Ran; Yu Tian; Bo-Han Wu; Wen-Bin Xiao (Geosciences)
In order to consider the effect of fabric anisotropy in the analysis of geotechnical boundary value problems, this study proposes a modified model based on a fabric-based modified Cam-clay model, which can account for the anisotropic response of soil. The major modification of the original model aims to simplify the equations for numerical implementation by replacing the SMP strength criterion with the Lade’s strength criterion. This model comprehensively considers the inherent anisotropy, induced anisotropy, and three-dimensional strength characteristics of soil. The model is first numerically implemented using the elastic trial–plastic correction method, and then it is encapsulated into the FLAC3D 6.0 software, and tested through conventional triaxial, embankment loading, and tunnel excavation experiments. Numerical simulation results indicate that considering anisotropy and three-dimensional strength in geotechnical engineering analysis is necessary. By accounting for the interaction between microstructure and macroscopic anisotropy, the model can more accurately represent soil behavior, providing significant advantages for geotechnical analysis.